Navigating diagnostic complexities and treatment strategies of Moyamoya syndrome: a case report - Kwan, Li Li; Abdul Rashid, Anna Misyail; Md Noh, Mohamad Syafeeq Faeez; Hoo, Fan Kee; Inche Mat, Liyana Najwa (Springer Science and Business Media LLC, 2024)
Moyamoya syndrome (MMS) is characterized by progressive narrowing of intracranial arteries and the development of collateral vessel networks, often presenting with recurrent ischemic or hemorrhagic strokes. MMS poses significant challenges in diagnosis due to its overlapping symptoms with other cerebrovascular conditions. Treatment aims to improve cerebral blood flow, reduce symptom frequency, and prevent future strokes. Management requires a multidisciplinary approach, including medical optimization and potential surgical intervention. This case report discusses a 37-year-old woman with poorly controlled type 2 diabetes and hyperlipidemia who experienced multiple strokes before being diagnosed with MMS. Initial symptoms included intermittent headaches, hemiparesis, and slurred speech. The presence of underlying metabolic conditions led to an initial assumption of atherosclerosis as the primary cause of her strokes. This case underscores the diagnostic challenge of distinguishing MMS from more common vascular conditions, highlighting the need for careful evaluation when typical risk factors like atherosclerosis do not fully explain recurrent cerebrovascular events.